Pengaruh Earning Per Share, Investing Cash Flow dan Economic Value Added terhadap Harga Saham pada Sub Sektor Otomotif dan Komponen yang Terdaftar di Bursa Efek Indonesia Periode 2015-2020 - Anggi Mahendra (Universitas Batanghari Jambi, 2021)
The stock price is a form of public trust in the company's performance. Stock prices are influenced by two factors, namely fundamental factors or factors related to the performance of a company and market factors (trust of investors and potential investors), factors that are determined from external to the company. The purpose of this study is to determine the effect of Earning Per Share (EPS), Investing Cash Flow (ICF), and Economic Value Added (EVA), on Stock Prices in Automotive and Component Sub-Sector Companies Listed on the Indonesia Stock Exchange for the 2015-2020 period. The population used in this study were 13 companies, and the sample was 5 companies using purposive sampling technique with the criteria set by the author. The analysis used is multiple linear regression analysis method. Based on the results of simultaneous testing, it is obtained that the variables Earning Per Share, Investing Cash Flow and Economic Value Added simultaneously have a very strong influence on the Stock Prices of Automotive and Component Sub-Sector Companies listed on the Indonesia Stock Exchange, so that the first hypothesis is proven and accepted. While the partial test results Earning Per Share has a positive and significant effect on stock prices, Based on the result of the study assisted SPSS software, the regression equation Z Score Y = 8,003E-18 + 0,838X1 – 0,131X2 – 0,057X3 + e Simulations the independent variables have a significant effect on the dependent variable which is indicated by fcount > ftabel and patially has a positive effect. R square 92,6% and rest 7,4% explain other variable outside research model